(3ef dG jMVQg Gdabjgs - (3Gdbej, GHf HGnHnhrjg, CHh LYaQ, GdUOhb, eMeO Hf Ydj Hf GdMSjf Hf ehSi, J (B381 (3gs
(3ChdgG (B:s
(3Gddge Efj CMeOc (B... (3aEfg deG SGbfj GdbVGA Edi HdGO GdZQHI hMqUdfj GdbOQ efgG HCQV HdN ef bUHI EjdGa hQOgG GdTQja GdOjf CHh YHO Gddg GdeYQha HfYeI Gddg hgh eMeO Hf GdMSjf Hf ESMGb (B.. (3aOGe HeLGdSJg SQhQj hGfTQM HePGcQJg UOQj (B...s
(3BNQgG (B:s
... (3hdbO MOKfj CHj Yf LOj Yf CHjg Ydjge GdSdGe Cf QShd Gddg Udi Gddg Ydjg hBdg bGd ef QBfj aj efGeg abO QBfj dCf GdTjWGf dG jJeKd aj UhQJj hdG aj UhQI (B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\ 274s
22\6841
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdMOjK hGdeUWdMs